Design model of cellular manufacturing system under the constraint of cost and delivery reliability - Bao, Weiwei; Kong, Fansen; Che, Haiyang (RISTI : Revista Ibérica de Sistemas e Tecnologias de Informação, 2016)
This paper presents a new design model of cellular manufacturing system, to meet the demand of the market, considering the cost and customer delivery constraints, to minimize the cost and maximize the system delivery reliability as the objective function of the model. Through the construction the cell, we can find the cell with good construction can achieve higher system reliability in the lower production cost at the same time, help in the face of fierce market competition. The cell is constructed by mathematical programming method, a multi-objective 0-1 integer programming model, the system reliability is redefined. The authors also take the reliability of delivery time as a main objective function, and it can meet the requirement of total cost and system delivery reliability by selecting suitable processing routes. In the establishment of the model, in order to facilitate the enterprise to make decisions, the introduction of a constraints in order to select the enterprise's own cellular manufacturing system design. Keywords: Delivery reliability, Cellular manufacturing system, Multi objective integer programming